2013
DOI: 10.1007/s00394-013-0510-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary cocoa ameliorates obesity-related inflammation in high fat-fed mice

Abstract: Purpose To investigate the effect of cocoa powder supplementation on obesity-related inflammation in high fat (HF)-fed obese mice. Methods Male C57BL/6J (n = 126) were fed with either low-fat (LF, 10 % kcal from fat) or HF (60 % kcal from fat) diet for 18 weeks. After 8 weeks, mice from HF group were randomized to HF diet or HF diet supplemented with 8 % cocoa powder (HF–HFC group) for 10 weeks. Blood and tissue samples were collected for biochemical analyses. Results Cocoa powder supplementation significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
101
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 39 publications
7
101
1
1
Order By: Relevance
“…Furthermore, the present data are consistent with other findings indicating that genistein promotes the expression of genes for fatty acid oxidation by induction of PPARα in human HepG2cells . Similarly, Cocoa treatment improved hepatic β-oxidation, via activation of PPARα-signalling in mouse livers (Fidaleo et al, 2014;Gu, Yu, & Lamert, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the present data are consistent with other findings indicating that genistein promotes the expression of genes for fatty acid oxidation by induction of PPARα in human HepG2cells . Similarly, Cocoa treatment improved hepatic β-oxidation, via activation of PPARα-signalling in mouse livers (Fidaleo et al, 2014;Gu, Yu, & Lamert, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…The increased bioavailability of NO may also mediate the beneficial effects of cocoa flavanols on endothelial function (53). Experimental studies have shown that cocoa supplementation slowed body weight gain, increased plasma concentrations of adiponectin, and attenuated insulin resistance, as indicated by improved HOMA-IR (54,55). In addition, a growing body of evidence derived from both in vitro studies and animal studies also demonstrates the antidyslipidemia and anti-inflammation effects of cocoa and cocoa flavanols (14, 56, 57) (58-60).…”
Section: Discussionmentioning
confidence: 99%
“…Black soybeans and sword beans fed to rats on a high-fat diet have been shown to decrease hepatic levels of TBARS [41], which is consistent with our results. Gu et al [36] have reported that cocoa supplementation decreased serum ALT and hepatic triglyceride levels, and suppressed liver inflammation in high-fat diet-fed mice. Our data indicate that in adzuki miso (AM) and black soybean miso (BSM) fermented for 6 months, DPPH scavenging activity was higher compared to soybean miso (M), which correlated with a significant reduction in serum AST and hepatic lipid peroxidation levels in mice on a high-fat diet.…”
Section: Effect Of Am and Bsm On Serum Ast And Hepatic Lipid Peroxidamentioning
confidence: 99%
“…Gu et al [36] have reported that dietary cocoa supplementation of high-fat diet for 10 weeks suppresses the increase of liver weight and ameliorates fatty liver disease symptoms in mice. The addition of adzuki polyphenol extract (APP) to drinking water used at a single dose reduced liver injury, liver weight, peroxide content, and serum AST in 11-week old ddY mice, suggesting that APP exerts hepatoprotective effects [5].…”
Section: Effects Of Am and Bsm On Food Intake And Body Organ And Fementioning
confidence: 99%